The determinants of the living wage among full time employees in East Malaysia / Nur Azureen Inchiem - Inchiem, Nur Azureen (2021)
Living wage can be defined as an income level that goes beyond just affording necessities such as food, shelter and clothes. It also includes the ability for an individual or a family to actively participate in society as well as to be free from financial distress. The living wage was introduced mainly in response to low wages and widening gap of income between low paid employees and high paid employees. Thus, for that reason people are facing problem to achieve the minimum acceptable living standard especially for those at the bottom household. Numerous countries all around the world have been implementing the living wage and each have been using several different methods to estimate the living wage. However, limited valuation of living wage has been done in Malaysia. Thus, this study attempts to determine the factors affecting the living wage in East Malaysia. This research utilizes electronic questionnaire as a main instrument in collecting data and the analysis of the data uses two main software which are Statistical Package for Social Science (SPSS) version 24 and Smart PLS 3.0 to identify the relationship between the independent and dependent variables. The findings for this study found that there is a relationship between expenditure of food, expenditure of housing, and expenditure of other essential needs towards the living wage for workers. It is as expected that different family size has different minimum acceptable living standard because different people would have different household expenditure and consumption pattern. This study can be used as a guideline to the policymaker or regulators to rectify the wages of Malaysian employees so that people are able to improve their standard of living.